Seminar on Computational Fluid Dynamics Applications in Biomedical Engineering: Book of Abstracts - Lima, Rui A. (Ed.) (2024)
Computational fluid dynamics (CFD) is a technique employed by engineers for more than 50 years to analyze heat transfer and fluid flow phenomena. In last years, there have been rapid developments in biomedical and health research applications of CFD. It has been employed to assess drug delivery systems, analyze physiological flows, assist in surgical planning (e.g., management of intracranial aneurysms), and innovate medical devices (e.g., vascular stents and valve prostheses). The complexity of these flows necessitate an interdisciplinary approach involving engineers, computer scientists, and mathematicians to create computer programs and software required to solve the mathematical equations. The advancement and progression of computational medicine will necessitate collaboration among specialists in engineering, computer science, and biomedical research. This seminar brought together a diverse community of experts, researchers, and practitioners dedicated to explore the transformative potential of CFD in addressing some of the most complex challenges in biomedical engineering. By simulating complex physiological flows to design next-generation medical devices, the abstracts contained herein reflect the knowledge exchanged during this event.